STATUS HUKUM PEREMPUAN MENURUT IBN ḤĀZM DAN KEDUDUKANNYA DALAM KOMPILASI HUKUM ISLAM (KHI) - M. Khoirul Hadi al-Asy’ari (Al-Ahkam, 2015)
This study based on library research that discusses the legal status of women in the view of Ibn Ḥāzm. This study intends to answer three important questions; first, how the circumstances of the biography of Ibn Ḥāzm and socio-historical culture that surrounds his life; second, how the thought of Ibn Ḥāzm about the legal status of women; third, is there any thought of Ibn Ḥāzm relevance to the concept of gender in islamic law compilation (KHI). This research is expected to contribute at least in three points of view; first, examine the biography of Ibn Ḥāzm and educational history and culture surrounding his social life; second, describe Ibn Ḥāzm’s modern thinking with regard to the legal status of women; and third, discover the extent of the relevance of his thinking on gender discourse in KHI. Using istiṣḥāb, Ibn Hazm concludes that women and men have the same high legal status. This thought even beyond the perspective of gender, human rights, multiculturalism, pluralism and democracy that are still not familiar with Indonesian ulama’. This is among the arguments that claimed as the reason for the failure of the initiative of KHI Counter Legal Drafting (CLD).